Malaysian Perception on E-Hailing Services ; Grab Vs. Maxim - Norsuraya Rosli; Nurul Nor Syafawati Sorfina Shaharum (CSR International Journal, 2023)
The purpose of this study is to identify the perception among Malaysians about e-hailing services in Malaysia. This study focuses on e-hailing passengers in Malaysia, especially Grab and Maxim. Therefore, the Internet is used to find information about e-hailing services. Questionnaires on Google Forms are also used as a data collection technique. As a result of this study, we get data from all of the data collection. The results of this study show that most users of e-hailing services are students. In addition, the results of this study determine that Grab is the main choice among users compared to Maxim. There are also those who think that the Maxim price is cheaper. The conclusion from this study is that everyone has a different perception. Some people think the e-hailing services are satisfactory, and some think otherwise. Even so, the e-hailing service has many users among Malaysians, such as students. Grab and Maxim are among the e-hailing services that have the most users.